Type-2 topology generated by type-2 fuzzy relation - AILLANE, WAFA; Sypervisor: SAADAOUI, Khaeir (UNIVERSITY of M'SILA, 2022)
Topology is one the branches of mathematics that has great received importance . In this memory, we studied the type-2 of fuzzy topology generated by type-2 fuzzy relations by expanding type-1 fuzzy topology generated by type-1 fuzzy relations .
Keywords: Type-2 fuzzy sets, type-2 fuzzy relations, type-2 fuzzy topology, fuzzy topology generated by fuzzy relation